Comparison of sensory shelf-life estimation of a beverage assessed in two locations - Elizagoyen, Eliana (2025)
Fil: Elizagoyen, Eliana. Instituto Superior Experimental de Tecnología Alimentaria. Departamento de Evaluación Sensorial de Alimentos; Argentina.